1995
DOI: 10.1046/j.1471-4159.1995.65052165.x
|View full text |Cite
|
Sign up to set email alerts
|

Cholinomimetics Increase Glutamate Outflow via an Action on the Corticostriatal Pathway: Implications for Alzheimer's Disease

Abstract: Physostigmine, the acetylcholinesterase inhibitor (0.3 mg/kg, i.m.), increased extracellular glutamate but not aspartate concentrations in the striatum of anaesthetised rats, determined using microdialysis and HPLC. The rise was both tetrodotoxin and calcium dependent. In contrast, neither physostigmine (10 µM) added to the perfusion fluid nor vehicle (injected intramuscularly) affected amino acid concentrations. To obtain evidence that the action of acetylcholine was to modulate positively cortical pyramidal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…However, various strategies aimed at different neurotransmitter systems actually alter the activity of glutamatergic neurons. For example, ACh esterase inhibitors increase the release of Glu (Dijk et al 1995b), while 5-HT 1A antagonism potentiates the effects of both muscarinic agonists and NMDA on Glu release (Dijk et al 1995a). Thus, it is possible that cognitive benefits of drugs directed at these targets involve actions on glutamatergic neurons.…”
Section: Discussionmentioning
confidence: 99%
“…However, various strategies aimed at different neurotransmitter systems actually alter the activity of glutamatergic neurons. For example, ACh esterase inhibitors increase the release of Glu (Dijk et al 1995b), while 5-HT 1A antagonism potentiates the effects of both muscarinic agonists and NMDA on Glu release (Dijk et al 1995a). Thus, it is possible that cognitive benefits of drugs directed at these targets involve actions on glutamatergic neurons.…”
Section: Discussionmentioning
confidence: 99%
“…35 There is evidence that cholinesterase inhibitors can promote the release of glutamate from pyramidal neurons, possibly by increasing cortical acetylcholine levels and subsequent activation of the cholinergic receptors. 40 In addition, it has been demonstrated that uncoupling of the postsynaptic muscarinic M1 receptor from G-proteins can correlate with the loss of N-methyl-D-aspartate (NMDA) receptor density and protein kinase C (PKC) activity in the postmortem frontal cortex of individuals with Alzheimer disease. 41 These results provide a neurochemical basis of interactions between cholinergic and glutamatergic systems and their potential implications in triggering pathological abnormalities in Alzheimer disease.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the afferent inputs to the cortex, acetylcholine is also released from local circuit neurons in this region (Cuello and Sofroniew, 1984;Houser et al, 1985), while acetylcholine M 1 receptors are localized to pyramidal neurons in the mPFC (Chessel et al, 1993). M 1 agonists, like PD 142505-0028 when injected into the PFC, activate pyramidal neurons as determined by increased dialysate glutamate concentrations in striatal regions (Dijk et al, 1995), and in turn acetylcholine produces excitatory effects in PFC that projects to ST. As M 1 receptors are correlated with glutamatergic stimulation, the decrease in M 1 receptors binding observed in the present study may indicate a possible occupation of these receptors by acetylcholine, contributing to animal's seizure activity and death. Based on an earlier work (Sanz et al, 1997), that noticed an increase in glutamate levels when M 1 receptors were activated, this excitatory aminoacid could play a role in cocaine-induced seizure and lethality in the PFC, when released indirectly after muscarinic receptor activation.…”
Section: Discussionmentioning
confidence: 99%